Expected effect of deposit insurance system over the state of the banking environment of Georgia - Sophio Khundadze (IBSU Scientific Journal (IBSUSJ), 2010)
The problem of weak market discipline, which is argued to be provoked by the implementation of deposit insurance system, is believed to be solved by imposing coverage limit over the insured funds. The paper focuses on the probable effects of deposit insurance system over the banking environment of Georgia through questioning and observing the behavior of Georgian population under deposit insurance system. The results of observation are tested using confirmatory data analysis to show the anticipated effect of the system and its component of coverage limit over the Georgian banking sector.
Keywords: 330; deposit insurance; coverage limit; market discipline